Smart Event Desk Mini Photovoltaic with Air Purifier FP-F30 - Khatami, Ahmad Azmi; Fithri, Normaliaty (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
At an event booth, there will undoubtedly be many visitors who will come to see the event and go around from one Booth to another. In a situation like this, the air in the booth environment will mix with visitors, from cigarette smoke to pollution outside the booth event so the air quality will be less good. Therefore, it is necessary to create an intelligent booth system to overcome pollution problems by equipping the Air Purifier at the event booth accompanied by lights, ultrasonic sensors, and mini photovoltaic. Mini photovoltaic serves as an alternative source of electrical power, supporting sensors such as ultrasonics to detect people around the Booth, humidity sensors, BH1750 light intensity sensors, voltage sensors, and lamps function as alternative lighting. Air Purifier will filter air pulsions around the event booth. This system works automatically, so it is more effective in its use